2018
DOI: 10.1002/cyto.a.23599
|View full text |Cite
|
Sign up to set email alerts
|

An integrated enrichment system to facilitate isolation and molecular characterization of single cancer cells from whole blood

Abstract: Circulating tumor cells (CTCs) carry valuable biological information. While enumeration of CTCs in peripheral blood is an FDA-approved prognostic indicator of survival in metastatic prostate and other cancers, analysis of CTC phenotypic and genomic markers is needed to identify cancer origin and elucidate pathways that can guide therapeutic selection for personalized medicine. Given the emergence of single-cell mRNA sequencing technologies, a method is needed to isolate CTCs with high sensitivity and specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A description of several of these EpCAM independent isolation methods can be found in this issue (39)(40)(41)(42)(43)(44)(45). A description of several of these EpCAM independent isolation methods can be found in this issue (39)(40)(41)(42)(43)(44)(45).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…A description of several of these EpCAM independent isolation methods can be found in this issue (39)(40)(41)(42)(43)(44)(45). A description of several of these EpCAM independent isolation methods can be found in this issue (39)(40)(41)(42)(43)(44)(45).…”
mentioning
confidence: 99%
“…Addition of fluorescently labeled antibodies recognizing treatment targets to the staining cocktail is relatively easy, although, one is limited by the number of fluorochromes that can be determined simultaneously. Tools to isolate the single cells from CTC enriched cell suspensions are available (39,41,42,56,57). Probing for gene aberrations of CTC by fluorescence in situ hybridization has also been demonstrated and again reiterated their extensive intra-and inter-patient heterogeneity (52)(53)(54)(55).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other systems are available to assess single cells, for example a self-sufficient micro-droplet generation system that facilitates encapsulation, chemical stimulation, and microscopic analysis of viable cells inside droplets [35]. However, many cells are used and it has not been shown that such systems work for rare cell populations like CTC single cell isolation technologies suitable for CTC analysis, including viable cells do exist like DEPArray™ [36], ALS cellselector™ [37] or FACS sorting [38] but no successful CTC cultures have been published yet. A workflow to successfully obtain viable CTC using self-sorting microwells is presented here.…”
Section: Discussionmentioning
confidence: 99%